Avaliação da dose fetal em radioterapia de mama, com câmara de ionização cilíndrica, usando blindagem e filtros físico e dinâmico - Filipov, Danielle (2010)
When a pregnant woman is submitted to breast radiotherapy, the fetus may be seriously affected by the peripheral dose. In order to verify that dose, a humanoid phantom, was irradiated at the left breast. The phantom is an adapted manikin, with some materials (densities close to water) inside and outside of it. The irradiation was done using a 6 MeV x-ray beam energy from a linear accelerator “Clinac 600C”. During the irradiation, a shield around the abdominal area of the manikin, consisting of blocks and slabs of lead was used. In addition, two types of filters were used: a physical, with 30o angulation, and an enhanced dynamic one. Through a cylindrical ionization chamber, positioned in the simulator ́s fetal region, it was found that, at the end of the breast treatment, the peripheral doses reach values between 3.90 and 48.67 cGy, when the physical wedge was used. With the application of the enhanced dynamic wedge, the values were between 1.75 and 13.78 cGy. According to the obtained data, the physical wedge can increase the peripheral dose due to the larger background radiation intensity and to the scattering caused by the attenuator material. In addition, the shielding couldn ́t block all the secondary radiation, which, according to the literature, can be able to induce mental retardation and cancer during postnatal life. However, the induction to these effects is negligible, when the type of wedge was changed.